Implementation of Supervision by the Secretary in Efforts to Achieve Effectiveness of Archives Management at the Secretariat of the Cooperatives and SMEs Office of North Sumatra Province - Zizah Chairani; Muhammad Arif (Penerbit Jurnal Indonesia, 2022)
In connection with the preparation of the research entitled